Uncontrolled hypertension and orthostatic hypotension in relation to standing balance in elderly hypertensive patients - Shen, Shanshan (Clin Interv Aging, 2015)
OBJECTIVE: To investigate the associations among uncontrolled hypertension, orthostatic hypotension (OH), and standing balance impairment in the elderly hypertensive patients referred to comprehensive geriatric assessment (CGA). METHODS: In a cross-sectional study, a total of 176 elderly hypertensive patients who underwent CGA were divided into OH group (n=36) and non-OH group (n=140) according to blood pressure measurement in the supine position, after immediate standing up, and after 1 minute and 3 minutes of standing position. Uncontrolled hypertension was defined as blood pressure of ≥140/90 mmHg if accompanied by diabetes mellitus (DM) or chronic kidney disease (CKD), or ≥150/90 mmHg if no DM and no CKD. Standing balance, including immediate standing balance and prolonged standing balance, was assessed in side-by-side and tandem stance. RESULTS: Neither uncontrolled hypertension nor OH was associated with prolonged standing balance impairment in elderly hypertensive patients (P>0.05). Blood pressure decrease after postural change was significantly associated with immediate standing balance impairment in side-by-side and tandem stance (P<0.05). Patients with OH were at greater risk of immediate standing balance impairment in both side-by-side and tandem stance than those without OH (odds ratio [OR] 3.44, 95% confidence interval [CI] 1.26–9.33, P<0.05; OR 3.14, 95% CI 1.14–8.64, P<0.01). Furthermore, uncontrolled hypertension was associated with immediate standing balance impairment in side-by-side stance (OR 2.96, 95% CI 1.31–6.68, P<0.05). CONCLUSION: Uncontrolled hypertension, OH, and blood pressure decrease after postural change were associated with immediate standing balance impairment, and therefore, a better understanding of the underlying associations might have major clinical value.